From solitude to solicitation: How people with intellectual disability or autism spectrum disorder use the internet - François Sallafranque-St-Louis; Claude L. Normand (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2017)
Very little is known about how people with intellectual disability (ID) or autism spectrum disorder (ASD) use the Internet. However, we do know that many of them have limited social circles. Electronic social media could facilitate the development of relationships, increase social participation and reduce social isolation for these people. However it may also expose users to unwanted encounters. Our exploratory study attempts to get a glimpse of Internet experiences of young adults with ID or ASD. Eight participants (five with ID and three with ASD) whose mean age was 25 years participated in this preliminary study. A sociodemographic and Internet use questionnaire was administered with the help of the participants’ support worker. Seven participants agreed to be interviewed by one of the researchers in a separate meeting, in the presence of their support worker. Results show that all participants enjoyed using the Internet for communicating (e.g. Facebook, e‑mail, chatrooms, dating sites) or entertainment (e.g. watching videos, listening to music). Three male subjects played games online, and only participants with ASD (without ID) created content (e.g. website or blog). All interviewees with ID and two of the three with ASD had distressing experiences including: being insulted online, having false rumors spread, receiving threats or being targets of sexual cyber-solicitation. Users with ID have had to rely on friends, parents or social workers to avoid or rectify cyber-victimization episodes. Internet access has opened a wide window of opportunity for people with ID and ASD, but more education and support is needed to ensure safe and positive Internet use by this population.